Macrotyloma axillare ‘Java’ presents structural and biochemical responses against Meloidogyne javanica - Angélica Miamoto; João Paulo Rodrigues Marques; Cláudia Regina Dias-Arieira (Frontiers in Plant Science)
The genus Meloidogyne is one of the most significant groups of plant-parasitic nematodes. Plant species capable of inhibiting the development and reproduction of this pathogen can be utilized as a management strategy. This study aimed to analyze the structural (constitutive and induced) and biochemical defense responses of the legume Macrotyloma axillare 'Java' in interaction with Meloidogyne javanica. The response of 'Java' to M. javanica was evaluated in two trials by inoculating 2000 eggs and second-stage juveniles (J2), with tomato used as a susceptible control. The reproduction factor (RF) was assessed 60 days after inoculation (DAI). Histochemical tests were conducted to observe constitutive and induced defense traits in 'Java' and tomato at 10, 20, and 30 DAI. Additionally, the reaction with 3,3'-diaminobenzidine was evaluated at 5 DAI, and root tips were examined using scanning electron microscopy at 30 DAI. The total protein content in roots was also measured at 8 and 12 DAI. In both trials, 'Java' showed RF < 1 (0.7 and 0.8) and was considered resistant to M. javanica, while tomato was susceptible, with RF > 1 (16.7 and 21.2). Histochemical analyses revealed constitutive defenses in 'Java', including the accumulation of phenolic compounds in phloem ducts and widespread suberin thickening in endodermal cells, whereas tomato exhibited only limited suberin thickening. Induced defenses in 'Java' included nematode females surrounded by cells with phenolic compound and protein accumulation, as well as deformed females and malformed giant cells with few cell wall invaginations at feeding sites. In tomato, feeding site development and nematode reproduction occurred without the accumulation of defensive compounds. Reaction with 3,3'-diaminobenzidine was more pronounced in 'Java' (42%) compared to tomato (23%). Scanning electron microscopy showed that giant cells in 'Java' were, on average, 46% smaller than those in tomato. Furthermore, 'Java' exhibited higher total protein levels when inoculated with M. javanica compared to the non-inoculated plant or tomato. In conclusion, 'Java' exhibits both constitutive and induced defense traits, which inhibit the full development and reproduction of M. javanica in its roots.